Simulasi Perancangan Press Tool Cylinder Head Gasket (3X –E 1181–00) Sepeda Motor Yamaha F1ZR - Basrullah Basrullah; Asmed Asmed; Nusyirwan Nusyirwan (Politeknik Negeri Padang, 2017)
Press tool is a press tool used to cut or form a thin plate into the desired shape with a pressing or press machine. This press tool is designed to be able to produce goods in bulk with a relatively short processing time without reducing the quality of the product, so that work efficiency can be improved and can reduce production costs. The design of the press tool for making cylinder head gaskets (3XA - E 1181 - 00) is a Yamaha F1ZR motor with a thickness of 0.5 mm made from ST37 through two processes, namely the embossing process, besides forming, the punch embossing also functions as a stripper. stock), followed by the cutting tool (piercing and blanking) process. Judging from the type of construction, this press tool belongs to the type of compound tool. In the process of making construction products this type has two workmanship functions but in one step work. The force that occurs is the sum of the cutting force (F _p = Us. R_m). The punch center calculation is useful for knowing the center of emphasis. This component is a gas leak retaining plate on the engine cylinder located between the cylinder block and cylinder head.